Extracranial Carotid Plaque Hemorrhage Is Independently Associated With Poor 3-month Functional Outcome After Acute Ischemic Stroke—A Prospective Cohort Study - Che, Fengli; Liu, Yanfang; Gong, Xiping; Wang, Anxin; Bai, Xiaoyan; Ju, Yi; Sui, Binbin; Jing, Jing; Geng, Xiaokun; Zhao, Xingquan (Frontiers in Neurology, 2021)
Background and Purpose: Carotid plaque hemorrhage (IPH) is a critical plaque vulnerable feature. We aim to elucidate the association between symptomatic extracranial carotid atherosclerotic IPH and poor 3-month functional outcome after acute ischemic stroke by high-resolution vessel wall MRI (HRVMRI). Methods: We prospectively studied consecutive patients with a recent stroke or transient ischemic attack(TIA) of carotid atherosclerotic origin. All patients underwent an HR VWMRI scan of ipsilateral extracranial carotid within one week after admission. Patients recruited were interviewed by telephone at 3-month. The primary outcome was a 3-month functional prognosis of stroke, expressed as a modified Rankin Scale (mRS) score. A poor prognosis was defined as a 3-month mRS score ≥ of 3. Univariate analysis was used to analyze the correlation between risk factors and IPH. The relation between IPH and 3-month functional outcome was analyzed by Cox regression analysis. Results: A total of 156 patients (mean age, 61.18±10.12 years; 108 males) were included in the final analysis. There were significant differences in the age, gender, smoking history, national institutes of health stroke scale (NIHSS) on admission, diastolic blood pressure (DBP) on admission between the IPH group and the non-IPH group (all p<0.05). During the follow-up, 32 patients (20.5%) had a poor functional outcome. According to the prognosis analysis of poor functional recovery, there was a significant difference between the two groups [36.7% vs. 16.7%; unadjusted hazard ratio (HR) 2.32, 95% confidence interval (CI) 1.12-4.81, p=0.024). Even after adjusting for confounding factors (such as age, gender, smoking history, National Institutes of Health Stroke Scale（NIHSS）on admission, DBP on admission, stenosis rate of carotid artery (CA), calcification, loose matrix, lipo-rich necrotic core (LRNC), and statins accepted at 3 months), IPH was still a strong predictor of poor 3-month outcome, and the adjusted HR was 3.66 (95% CI 1.68-7.94, p=0.001). Conclusions: Extracranial carotid IPH is significantly associated with poor 3-month outcome after acute ischemic stroke and can predict the poor 3-month functional prognosis.